2020
DOI: 10.1080/14775085.2020.1850322
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental tourism activities: a conceptual framework to maximise sport tourism benefits and opportunities

Abstract: Theoretical integration has been called for in sport tourism research in order to capture the synergies of existing contributions. In response, this article proposes a conceptual framework of supplemental tourism activities, which are motivated by secondary and/or tertiary tourism attractions that complement or reinforce tourism benefits and opportunities bestowed by a primary tourism attraction. This is achieved by integrating the sport and non-sport interactions into Hinch and Higham's (2001) sport tourism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Another emerging sector in Cyprus is sport tourism, which is defined as sport-based travel away from the home and where sport based and non-sport activities are integrated (Ito and Higham, 2020). The emergence of sport tourism in Cyprus happened when the British Mitigating the effects of tourism seasonality Olympic Committee selected Cyprus as a training destination to prepare athletes for the Olympic Games in Greece; however, early on it was identified that collaborative efforts are necessary to develop Cyprus as a sports destination beyond one event (Kartakoullis and Karlis, 2002).…”
Section: Sport Tourismmentioning
confidence: 99%
“…Another emerging sector in Cyprus is sport tourism, which is defined as sport-based travel away from the home and where sport based and non-sport activities are integrated (Ito and Higham, 2020). The emergence of sport tourism in Cyprus happened when the British Mitigating the effects of tourism seasonality Olympic Committee selected Cyprus as a training destination to prepare athletes for the Olympic Games in Greece; however, early on it was identified that collaborative efforts are necessary to develop Cyprus as a sports destination beyond one event (Kartakoullis and Karlis, 2002).…”
Section: Sport Tourismmentioning
confidence: 99%
“…Although the scale and magnitude of its impacts are obvious in the recent publications by sport tourism scholars (e.g. Ito and Higham, 2020; Weed, 2020), the number of studies that assess the recovery strategies is still limited. It is well known that the uniqueness of each crisis, the sociopolitical environment at the time of a crisis, and the overall tourism structure in each destination complicates the tourism crisis management procedures (Henderson, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Resilience planning to handle the potential life-threatening crises that also damage the reputation of host destinations and communities becomes even more important in sport tourism since the gathering of a large number of spectators in venues creates an inflated perception of risk that subsequently impacts tourists' intentions and behavior (Shipway, 2018). Considering that COVID-19 caused greater damage in the USA than any other infectious disease, implementing recovery strategies and building resilience to confront current and future crises become more important than ever (Ito and Higham, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this region, social and organized tourism activities, such as the Eastern Anatolia International Youth Festival, under the wings of my Anoatolia, in which I have families in 81 cities, International bird watching festivals, International ice climbing festival, Traditional wrestling competitions, such as setting up boarding houses, physical tourism investments in hotels and accommodation were also realized. Creating opportunities associated with sport tourism and supplemental tourism activities can help regional and national tourism organizations to maximize the tourism benefits [69]. Generally, tourism activities in the Uzundere region are as follows: (1) In the field of cultural tourism, you can visit cultural heritage phenomena such as Engüzekkapı Castle, Öşk Monastery, Kireçli Bridge,İnçer Mosque, Sapaca Mosque, and Sapaca Castle.…”
Section: Rural Tourism In Uzunderementioning
confidence: 99%